2013
DOI: 10.1177/2042098613477125
|View full text |Cite
|
Sign up to set email alerts
|

Systems that prevent unwanted represcription of drugs withdrawn because of adverse drug events: a systematic review

Abstract: Represcription of medication that was withdrawn after the occurrence of an adverse drug event (including allergy), is a recognized medication safety issue on a patient level. We performed a systematic review to identify systems (electronic and nonelectronic) that can prevent the represcription of drugs withdrawn because of an adverse drug event and the effects of these systems. The review was performed using PRISMA and Cochrane guidelines. PubMed and Embase were searched for articles describing systems that ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 42 publications
0
29
0
Order By: Relevance
“…Despite limited evidence that these systems are effective, some studies confirmed that the rate of adverse reactions caused by readministration of the suspected culprit drug decreased substantially after the introduction of the surveillance system. 37,38 Our study suggests that most prescriptions of antiepileptic drugs were appropriate. Epilepsy was the more frequent indication for aromatic and nonaromatic antiepileptic drugs, but antiepileptic drugs were also commonly prescribed for other indications such as bipolar disorder or neurological pain.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Despite limited evidence that these systems are effective, some studies confirmed that the rate of adverse reactions caused by readministration of the suspected culprit drug decreased substantially after the introduction of the surveillance system. 37,38 Our study suggests that most prescriptions of antiepileptic drugs were appropriate. Epilepsy was the more frequent indication for aromatic and nonaromatic antiepileptic drugs, but antiepileptic drugs were also commonly prescribed for other indications such as bipolar disorder or neurological pain.…”
Section: Discussionmentioning
confidence: 74%
“…For instance, multiple electronic systems have been developed to prevent the readministration of drugs that were withdrawn because they caused an adverse drug reaction. 37 In all systems, a documented allergy triggered an alert to avoid represcription. Despite limited evidence that these systems are effective, some studies confirmed that the rate of adverse reactions caused by readministration of the suspected culprit drug decreased substantially after the introduction of the surveillance system.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, to address post-discharge DRPs in the most efficient way with the highest impact, evidence tends to focus on discharge planning combined with home-based followup strategies [4]. The importance of adequate follow-up across healthcare settings is further illustrated by the fact that 27 % of drug treatments withdrawn during hospitalization as a result of an adverse drug reaction, had been represcribed post-discharge [10]. Additionally, a high number of readmissions occur in the days to weeks following hospital discharge of which a substantial percentage is drug-related [3].…”
Section: Pharmacist Interventionsmentioning
confidence: 99%
“…
Effectiveness of drug allergy card to prevent repeated prescribing of allergenic medications in a Malaysian public hospital To the editor:Information regarding drug allergy is often poorly documented in health care settings. [1][2][3] Despite being preventable, the repeated prescribing of known allergenic medications is still common, accounting for 8% to 15% of the medication errors worldwide. 2,[4][5][6][7] In response to the global concern about drug safety, the European Academy of Allergy and Clinical Immunology has recommended the use of drug allergy cards.
…”
mentioning
confidence: 99%
“…[1][2][3] Despite being preventable, the repeated prescribing of known allergenic medications is still common, accounting for 8% to 15% of the medication errors worldwide. 2,[4][5][6][7] In response to the global concern about drug safety, the European Academy of Allergy and Clinical Immunology has recommended the use of drug allergy cards. 8 This method has long been implemented in public hospitals in Malaysia as a strategy to facilitate the communication of patients' drug allergy history, especially during emergency situations in which complete medical records and medication history are usually not available.…”
mentioning
confidence: 99%